Analyzing the Effect of Prime Services Provided by Hajj And Umrah Organizing Section at the Ministry of Religion Office in Pariaman Municipality on Prospective Hajj Pilgrim’s Satisfaction - Putri, Friska Etvari; Puteri, Hesi Eka (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
This study aims to disclose how the prime services provided by the Hajj and Umrah Organizing Section of Ministry of Religion in Pariaman Municipality affects the satisfaction of prospective pilgrims. This study offered quantitative data. The sample was taken using quota sampling. The research used primary data collected from respondents by distributing 93 questionnaires. The data were analyzed using simple linear regression, classical assumption test, and hypothesis test assisted by SPSS 20 application. Based on the significance value of <0.01 or X 0.000 <0.01 for the relationship between the prime service variable (X) and the pilgrim’s satisfaction (Y), Ho was rejected and Ha was accepted. This indicated that prime service (x) was associated with pilgrim’s satisfaction (y). Based on this research’s findings, it could be inferred that the quality services provided by the Ministry of Religion in Pariaman Municipality influenced the prospective pilgrim’s satisfaction. Thus, it is recommended that the Hajj and Umrah Organizing Section keeps on improving their service quality to ensure that prospective pilgrims remain satisfied.